The Implementation Of Regulation Of The Minister Of Trade Number 51/M-Dag/Per/7/2015 Concerning The Prohibition Of Importing Second-Hand Clothes In Surakarta City - Aulia Firdausy, Kharisma; Sentot Sudarwanto, Albertus (CV. Inara, 2022)
The sale and purchase of second-hand imported clothes (thrifting) that were now commonly found in Surakarta city make authors interested in examining how the implementation of Minister of Trade Regulation No. 51 of 2015, what factors and reasons as the causes of the rampant sales ofsecond-hand imported clothes in Surakarta City, how were the efforts of the Surakarta City government itself in overcoming the rampant sales of second-hand imported clothes. The study objectives consisted of determining the factors causing the rampant sales of second-hand imported clothes in Surakarta City, finding out the factors and reasons for the practice of buying and selling second-hand imported clothes, and finding out the role of the Surakarta City government in dealing with the problem of buying and selling secondhand imported clothes. The research method was qualitative, and the author used a normative sociological approach. In contrast, the sociological/empirical legal studyexamined primary data obtained directly in the field. There were some problems between sellers of second-hand imported clothes and the Indonesian government.It was because sellers entered the second-hand imported clothes illegally, which was tantamount to not complying with the rules made by the government.